Regulatory mechanisms and clinical implications of PIWI-interacting RNAs (piRNAs) in major digestive tract cancers - Penghui Li; Yuan Xue; Xinyu Gu (Cancer Cell International)
Abstract Cancers of the digestive tract, including those affecting the esophagus, stomach, liver, pancreas, and colorectum, impose a substantial global health burden due to their high morbidity and mortality rates. Despite advancements in diagnostic and treatment modalities, the molecular mechanisms underpinning the initiation and progression of digestive tract cancers remain incompletely understood. Recent progress in high-throughput sequencing technology has uncovered the crucial role of small non-coding RNAs (ncRNAs) in regulating gene expression and maintaining genomic stability across various cancers, including those affecting the digestive tract. P-element-induced wimpy testis (PIWI)-integrating RNAs (piRNAs), a subset of small ncRNAs, emerge as pivotal regulators in preserving genome integrity by suppressing transposable elements in germline cells. Growing evidence implicates piRNAs in the development and advancement of digestive tract cancers. Notably, piRNAs exhibit complex and multifaceted roles in these tumors, functioning as both tumor suppressors and oncogenes. They exert their effects through diverse mechanisms, including post-transcriptional gene silencing, epigenetic modifications, and modulation of signaling pathways involved in tumorigenesis, such as the Wnt/β-catenin, PI3K/Akt, and MAPK pathways. Dysregulation of piRNAs disrupts key cellular processes, including cell cycle regulation, apoptosis, epithelial-mesenchymal transition, and metastasis, across various digestive tract cancers. Moreover, distinct expression profiles of specific piRNAs correlate with diverse clinical features and outcomes in individuals afflicted with digestive tract cancers, highlighting their potential as diagnostic and prognostic biomarkers in this context. Furthermore, therapeutic interventions targeting dysregulated piRNAs or their downstream effectors hold promise as novel avenues for precision medicine approaches in managing digestive tract cancers. In this review, we summarize the current understanding of piRNAs in digestive tract cancers, focusing on their dual roles as both tumor suppressors and oncogenes. We further delve into the intricate molecular mechanisms by which piRNAs modulate crucial cellular processes implicated in tumorigenesis. Additionally, we explore the potential of piRNAs as valuable diagnostic, prognostic, and therapeutic biomarkers in the landscape of digestive tract cancers. By elucidating the complex interplay between piRNAs and digestive tract cancers, this review aims to offer insights into novel therapeutic strategies centered around targeting piRNAs for precision medicine approaches in the management of these malignancies.